AN ANALYSIS OF WOMEN AGRICULTURAL LABOURERS AT SRIVAIKUNDAM IN THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Over 70% of Indians depend on agriculture and allied jobs for a living. Women are essential to economic growth. In 1/3 of households, women contribute 50% of the total earnings. They contribute 2/3 of the world's work hours, 50% of the world's food, 60% of the work force, and 30% of the official labour force. The study focuses on women's role in paddy cultivation, farm operations, household decision-making, challenges they face, ideas, and policy actions. India's most important industry is agriculture. This popular sector has contributed to the increased pace of the economy's changes and bigger revolution. Agricultural women labourers are unorganised, unskilled, non-migratory, have no legal protection, and have difficult relationship with landowners. According to the study, agricultural women labourers in the study area needed better working conditions. Their work hours should be regulated. Overtime pay should be given for extra hours. Improve agricultural women labourers' socioeconomic environment. The state can provide health centres, maternity wards, youth clubs, and sports facilities. Special programmes for agricultural women labourers can be arranged.